Identification of Small Molecule Modulators Targeting TLR7 and TLR9 Signaling Pathways - 최보금 (The Graduate School, Ajou University, 2024)
Toll-like receptors (TLRs) are pivotal in innate immunity, recognizing pathogen-associated and endogenous danger signals to trigger inflammatory responses. Dysregulated TLR signaling is implicated in autoimmune diseases such as systemic lupus erythematosus (SLE), rheumatoid arthritis, and inflammatory bowel disease. Specifically, TLR7 and TLR9 are essential for detecting viral RNA and unmethylated CpG DNA, respectively, which leads to immune activation and cytokine production. In this study, a novel computationally designed inhibitor IM45, demonstrates the ability to selectively target TLR7/9-mediated inflammation without impacting other TLR pathways. Mechanistic investigations reveal that this inhibitor effectively suppresses MAPK phosphorylation and NF-κB activation, critical steps in the regulation of inflammatory cytokines. The selective inhibition underscores the potential of this inhibitor as a promising therapeutic strategy for managing TLR7/9-associated autoimmune disorders, warranting further clinical validation for future therapeutic applications. Key words: TLR7, TLR9, Immune modulation, TNF-α production, ELISA
학위논문(석사)--분자과학기술학과,2024. 8
Keywords: antagonist; tlr7/9